EXTENSIVE READING ON ACCURACY, ACCEPTABILITY, AND READABILITY IN TRANSLATION STUDY - Irawati, Tatik (IKIP Mataram, 2019)
The purpose of this study was to determine the effect of extensive reading on the ability to translate scientific and non-scientific articles. Translation techniques that often appear a literal translation, adaptation, discursive creation, borrowing, generalization, and calque. Whereas translation methods use a free translation, adaptation, faithful translation, word for word translation. The research method used experimental quantitative with subject 35 in class A and B. The extensive reading value of 25% had the highest score between 81-92, then 45% had average reading ability between 66-80 and 30% low or level the reading is not good with a value of 0-65. Significant between the two is 80% indicating the level of quality of translation results is good if the ER is high.